Features of the Course of Radioinduced Breast Cancer. Clinical Observation - M. M. Zamilov; K. V. Menshikov; Sh. I. Musin; A. V. Sultanbaev; G. I. Zamilova; A. H. Nguyen (Креативная хирургия и онкология)
Introduction. Hodgkin’s lymphoma is most commonly reported in the young age of 20 to 40 years. Radiation therapy remained the first-choice option before the advent of modern chemotherapy agents. Thereafter, the risk of radioinduced breast cancer after radiotherapy with total radiation dose of 38 Gy or more increased 4.5-fold.Materials and methods. The presented clinical case demonstrates aggressive breast cancer that developed 43 years after radiation therapy for Hodgkin's lymphoma.Results and discussion. In the 1990s, chemotherapy regimens for Hodgkin’s lymphoma were not effective enough to control the disease, therefore, radiotherapy was an indispensable measure. Secondary radioinduced tumors take the second place (26 %) in the structure of mortality from Hodgkin’s lymphoma. The emergence of new, more effective chemotherapy regimens reduced the risk of secondary tumors and, in particular, breast cancer.Conclusion. At present, up to 75 % of patients with Hodgkin’s lymphoma can be cured using modern methods of chemotherapy and radiation therapy. In follow-up care, it is necessary to consider the high risk of secondary malignant neoplasms, especially lung and breast cancer.